2013
DOI: 10.1016/j.ajo.2013.06.022
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Ophthalmoscopy to Medical Students (the TOTeMS Study)

Abstract: Purpose To determine medical student preferences for learning the ocular fundus examination and to assess their accuracy using different examination modalities. Design Prospective, randomized study of medical student education approaches. Methods First-year medical students received training in direct ophthalmoscopy using simulators and human volunteers. Students were randomized to receive vs. not receive specific training on interpreting fundus photographs prior to accuracy assessments. Students’ preferen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
76
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(83 citation statements)
references
References 19 publications
1
76
1
3
Order By: Relevance
“…However, we found a higher percentage compared to that seen in the TOTeMS study, in which 49% of students indicated they would perform direct ophthalmoscopy as part of the general physical examination (Kelly et al, 2013).…”
Section: Discussioncontrasting
confidence: 48%
See 2 more Smart Citations
“…However, we found a higher percentage compared to that seen in the TOTeMS study, in which 49% of students indicated they would perform direct ophthalmoscopy as part of the general physical examination (Kelly et al, 2013).…”
Section: Discussioncontrasting
confidence: 48%
“…Among the proposed models include: styrofoam head with a holder for photographs; table tennis ball with printed words in its inner rear face; and plastic containers with retinal photographs in the bottom (Chung & Watzke, 2004). The TOTeMS study ( Kelly et al,2013) used plastic containers with fundus photography adhered to the back of the container to evaluate the medical student direct ophthalmoscopy teaching. Their conclusion was not favorable to the use of simulators, because the students preferred learning by fundus photography.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even when direct ophthalmoscopy is performed, students and physicians demonstrate a lack of confidence in their findings, further minimizing the ability of the ocular fundus examination to positively affect patient care. 7 Ophthalmoscopy has long been considered an essential part of the physical examination in patients with headache. Whereas most patients with headache who visit an emergency department have a primary headache syndrome, the detection of optic disc edema is indispensible in determining which patients have a more serious underlying cause.…”
Section: Ophthalmoscopy In Clinical Practicementioning
confidence: 99%
“…The TOTeMS study 7 concluded that students preferred fundus photographs for both learning and examining the ocular fundus, with 70% saying they would prefer to have fundus photographs instead of using the ophthalmoscope during upcoming clinical rotations. When tested, students' answers were significantly more accurate when interpreting fundus photographs than when performing ophthalmoscopy.…”
mentioning
confidence: 99%